Development of a community health inclusion index: an evaluation tool for improving inclusion of people with disabilities in community health initiatives. (December 2015) - Eisenberg, Yochai; Rimmer, James; Mehta, Tapan; Fox, Michael
Abstract Background Community health initiatives often do not provide enough supports for people with disabilities to fully participate in healthy, active living opportunities. The purpose of this study was to design an instrument that focused on integrating disability-related items into a multi-level survey tool that assessed healthy, active living initiatives. Methods The development and testing of the Community Health Inclusion Index (CHII) involved four components: (a) literature review of studies that examined barriers and facilitators to healthy, active living; (b) focus groups with persons with disabilities and professionals living in geographically diverse settings; (c) expert panel to establish a final set of critical items; and (d) field testing the CHII in 164 sites across 15 communities in 5 states to assess the instrument's reliability. Results Results from initial analysis of these data indicated that the CHII has good reliability. Depending on the subscale, Cronbach's alpha ranged from 0.700 to 0.965. The CHII's inter-rater agreement showed that 14 of the 15 venues for physical activity or healthy eating throughout a community had strong agreement (0.81 – 1.00), while one venue had substantial agreement (0.61 – 0.80). Conclusion The CHII is the first instrument to operationalize community health inclusion into a comprehensive assessment tool that can be used by public health professionals and community coalitions to examine the critical supports needed for improving healthy, active living among people with disabilities.